Primary sternal tumour resection and reconstruction with LARS mesh-bone cement sandwich by 3D-printing: Case reports - Zhang, He; Hou, Bo; Xia, Tienan; Ji, Lu; Li, Jiatong; Chen, Ting; Shang, Guanning (Frontiers in Bioengineering and Biotechnology, 2023)
Background: There are many reconstruction methods after sternal tumor resection, but the method that LARS mesh combines with bone-cement has not been reported. Case report: A 54-year-old female patient and a 55-year-old male patient admitted to our department all presented with sternum masses, but neither presented with respiratory disorders. In women with limited manubrium sternum lesions, we resected the manubrium sternum completely. In men with sternal lesions, we removed part of the sternum and part of the sternocostal joint. The patient recovered well after surgery, and there were no respiratory complications and no tumor recurrence during the 1-year follow-up. Conclusion: We report two cases of sternal defect repair using LARS mesh combined with bone cement. This method is safe and stable, and can achieve satisfactory results.